Risk factors and management of biliary leakage after endocystectomy for hepatic cystic echinococcosis - Abbasi Dezfouli, Sepehr; El Rafidi, Ahmad; Aminizadeh, Ehsan; Ramouz, Ali; Saeedi, Mohammed al; Khajeh, Elias; Mieth, Markus; Weber, Tim; Chang, De-Hua; Hoffmann, Katrin; Büchler, Markus W.; Mehrabi, Arianeb (PLoS neglected tropical diseases, 2023)
Background Endocystectomy is a conservative surgical approach to managing cystic echinococcosis. Bile leakage is the main complication of this technique. The aim of this study was to evaluate the factors associated with bile leakage and to assess the outcomes and cost efficiency of strategies used to treat bile leakage. Methodology/Principal findings Patients who underwent endocystectomy between 2005 and 2020 were included. The preoperative characteristics, intra- and postoperative outcomes, hospital costs, and cost efficiency (the Diagnosis-Related Group reimbursement minus the overall cost) were evaluated prospectively. A total of eighty patients with 142 cysts were included. Postoperative complications occurred in 17 patients (21%), including 11 patients with bile leakage (type A: 1, type B: 6 and type C: 4 patients, total 13%). Bile leakage was more frequent in patients with preoperative MRI signs of cysto-biliary fistulas or intraoperative visible cysto-biliary fistulas (p = 0.03 and p = 0.04, respectively) and in patients with cysts larger than 8 cm (p = 0.03). Patients with bile leakage who underwent reoperation (type C) had significantly shorter hospital stays (9 vs. 16 days, p<0.01) and better cost efficiency than those who received radiologic or endocscopic interventions (€2,072 vs. -€2,097 p = 0.01). No mortality was observed, and recurrence was seen in two patients. Conclusions/Significance Endocystectomy is a safe and efficient technique. Preoperative and intraoperative cysto-biliary fistulas and a cyst diameter larger than 8 cm are correlated to postoperative bile leakage. Early operative management of bile leakage reduces hospital stay and improves cost efficiency compared with radiologic or endoscopic treatments.